Private health sector assessment in Tanzania - White, James, 1980- (World Bank studies., 2013)
Mainland Tanzania exemplifies the developing world's struggle to achieve middle-income status while confronting widespread poverty and substantial health challenges. Tanzania's struggle with HIV/AIDS, reproductive and child health, malaria, and tuberculosis are characterized by both positive recent trends and persistent challenges. A high disease burden coupled with finite public sector resources has led the government of Tanzania to increasingly seek innovative tools to protect the health and wellbeing of its citizens. Previous reform efforts have included decentralizing decisionmaking author.